PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PEER LESSONS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Dessy Triana Relita; Anna Marganingsih; Utari Ilhayati Ningsih (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Background of this research was critical thinking ability of students who have not developed maximally in the learning process. During this time, the implementation of learning is dominated by the use of lecture methods that are more teacher-centered activities. This research used quantitative approach, quasi experimental method with design Nonequivalent Control Group. The population in this study was all students of class X with the number of 68 students. The data collection tools used was test questions, observation sheets, questionnaires, and documentation. Based on the data analysis, the following research results are obtained: (1) learning implementation in the experimental class and control class showed excellent results, need good preparation, and was supported by good interaction between teachers and students. Testing the hypothesis proves that there is a significant difference of critical thinking ability of experimental class and control class on the final measurement (posttest) is indicated by z count> z table or 2,30> 1,96 which means Ho refused and Ha accepted. (2) Result of student’s questionnaire response after done data processing, obtained average value 90,66% with very strong category, so it can be concluded that active learning strategy of peer lesson type can be applied as one of strategy in economic learning.